Potentials of mono- and multi-metal ion removal from water with cotton stalks and date palm stone residuals - Heba Nagy; Manal Fawzy; Elsayed Hafez; Alaa El Din Mahmoud (Environmental Science and Pollution Research, 2023)
In this work, cotton stalks ( Gossypium barbadense ) and date palm stones ( Phoenix dactylifera ) have been used as biosorbents to remove cadmium; Cd(II), lead; Pb(II), and zinc; Zn(II) from mono- and multi-solutions. Each biosorbent was characterized using SEM-EDX, and FT-IR. The findings showed that pH, dose, contact time, metal concentration, and particle size affect the treatment process. The adsorption pattern was Pb(II) > Cd(II) > Zn(II) for both biosorbents. The adsorption performance of cotton stalks was higher than that of date palm stones. The fitted maximum uptake capacities; q m of cotton stalks were higher than those of date palm stones. The maximum adsorption at optimum conditions of Pb(II), Cd(II), and Zn(II) with cotton stalks were 98%, 92.1%, and 78.9%, respectively, within 30 min. While the maximum adsorption of Pb(II), Cd(II), and Zn(II) with date palm stones were 94.6%, 76%, and 68.6%, respectively. Results confirmed the antagonistic effect of heavy metal removal at optimum conditions. Biosorbents could remove ~ 100% of the metal ions from real wastewater samples. Regeneration investigation revealed a successful reusability of both biosorbents for four cycles.